High Efficient Antioxidant Activity of Extracts from Lepidium meyenii Walp. - Wang, L.W.; Liang, J.; Wang, X.D.; Yuan, X.F.; Zhao, B.; Yang, Y.W. (Asian Journal of Chemistry, 2012)
The antioxidant activities of petroleum ether extract (E1), chloroform extract (E2), ethyl acetate extract (E3), n-butanol extract (E4), ethanol extract (E5) and deionized water extract (E6) obtained from Lepidium meyenii Walp. were investigated using various in vitro methods, which were reducing power and scavenging activities towards 1,1-diphenyl-2-picryhydrazyl (DPPH) radical, superoxide radical and hydroxyl radical. The amounts of total phenolic in the extracts were analyzed and determined by spectrophotometric methods. The n-butanol extract was found to have high levels of phenolic content (44.78 mg GAE/g) and higher reducing power. The n-butanol extract showed the most potent radical-scavenging activity on DPPH radicals and superoxide anion radicals, with IC50 values of 1.06 mg/mL and 0.30 mg/mL, respectively. There was a significant correlation between total phonolic content and total antioxidant activity (r2 = 0.986). The n-butanol extracts of Lepidium meyenii Walp. might be valuable antioxidant natural sources and seemed to be applicable in both healthy medicine and food industry.